Rethinking children's agency: Power, assemblages, freedom and materiality. Issue 3 (September 2019) - Gallagher, Michael
This article attempts to rethink agency for childhood studies, drawing on Foucault's theorisations of power, Deleuze and Guattari's concept of assemblage, Bennett's vital materialism and Grosz's account of Bergson's conception of freedom. I argue that (1) agency is ambivalent, that is, it has no intrinsic ethical value; (2) agency is not a property of individual children but happens within assemblages; (3) it is analytically useful to distinguish between more routine and more inventive tendencies of agency; and (4) agency arises in the relations between the organic and the inorganic, as life actualises the virtual potential of matter for indeterminacy. These ideas contribute to ongoing debates about agency within the field, and connect these debates with wider questions about children's relations with materials and nonhumans.